1977
DOI: 10.1073/pnas.74.1.211
|View full text |Cite
|
Sign up to set email alerts
|

Density of sodium channels in mammalian myelinated nerve fibers and nature of the axonal membrane under the myelin sheath.

Abstract: Density of sodium channels in mammalian myelinated nerve fibers and nature of the axonal membrane under the myelin sheath Communicated by Alfred Gilman, October 26, 1976 ABSTRACT The density of sodium channels in mammalian myelinated fibers has been estimated from measurements of the binding of [3Hjsaxitoxin to rabbit sciatic nerve. Binding both to intact and to homogenized nerve consists of a linear, nonspecific, component and a saturable component that represents binding to the sodium channel. The maxim u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
145
3

Year Published

1980
1980
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(154 citation statements)
references
References 28 publications
6
145
3
Order By: Relevance
“…In the internodal axonal membrane, the voltage-dependent sodium channel is found at concentrations of 20 -25 channels/m 2 , compared with concentrations ranging from 1000 channels/m 2 (Shrager, 1989) to 12,000 channels/m 2 (Ritchie and Rogart, 1977) at the node of Ranvier. The asymmetric distribution of ion channels in the myelinated axon and the regular spacing of these nodes at ϳ100 times the axonal diameter (Rushton, 1951;Chiu, 1980) are critical for the fast conduction velocities associated with these axons and represent an interesting problem in cell polarity and membrane differentiation.…”
Section: Abstract: Node Of Ranvier; Cell Adhesion Molecules; Ankyrinmentioning
confidence: 99%
“…In the internodal axonal membrane, the voltage-dependent sodium channel is found at concentrations of 20 -25 channels/m 2 , compared with concentrations ranging from 1000 channels/m 2 (Shrager, 1989) to 12,000 channels/m 2 (Ritchie and Rogart, 1977) at the node of Ranvier. The asymmetric distribution of ion channels in the myelinated axon and the regular spacing of these nodes at ϳ100 times the axonal diameter (Rushton, 1951;Chiu, 1980) are critical for the fast conduction velocities associated with these axons and represent an interesting problem in cell polarity and membrane differentiation.…”
Section: Abstract: Node Of Ranvier; Cell Adhesion Molecules; Ankyrinmentioning
confidence: 99%
“…The density of voltage-gated ion channels throughout the plasma membrane is finite. For example, in muscle fibres, the density of the voltage-gated sodium channels was estimated to be 380 channels per mm 2 (Almers & Levinson 1975), whereas in mammalian myelinated nerve fibres, the density of sodium channels can be as high as 12 000 per mm 2 in nodal areas and as low as 25 channels per mm 2 in internodal areas (Ritchie & Rogart 1977). Thus, a disadvantage of electrodes with small surface area is the relatively low current that can be generated by the membrane patch in contact with the electrode or the number of passive ion channels through which current can flow.…”
Section: Estimate Of the Seal Resistance Formed Bymentioning
confidence: 99%
“…On the other hand, analysis of membrane currents in demyelinated nerve fibres from alloxan diabetic rats (Brismar, 1979), in diphtheria toxin-treated nerves (Bostock, Sears & Sherratt, 1981;Brismar, 1981) or after acute myelin loosening treatments (Chiu & Ritchie, 1981 showed that K, but not Na channels are present under the internodal myelin of mammalian or amphibian nerve fibres. Interestingly, Na channels which are restricted to the nodal membrane under normal conditions (Ritchie & Rogart, 1977) appear at the internodes as a consequence of demyelination by diphtheria toxin (Bostock & Sears, 1978;Brismar, 1981;see Waxman & Foster, 1980, for review).…”
Section: Introductionmentioning
confidence: 99%